Development Of Blog “Hi Si IPA” On Ecosystem Materials To Improve Science Literacy For Students Grade V In Elementary School - Dini Rosyada Mahmud; Shirly Rizki Kusumaningrum; Radeni Sukma Indra Dewi (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2022)
Learning media is an important part of the learning process. Students grade V need learning media blog to make it easier for understand learning material for theme ecosystems. Learning media blog has never been used in ecosystem materials in elementary school. The method used in this research and development using five stages: the model ADDIE (Analysis-Design-Development-Implement-Evaluate). Quantitative data analysis use to process the data results in numbers obtained from filling out validation questionnaires by learning media experts and material experts. Qualitative data take from the suggestions and input of material experts, learning media experts, students, and teachers who perfected the learning media of the blog